2015
DOI: 10.30552/ejihpe.v4i3.85
|View full text |Cite
|
Sign up to set email alerts
|

Estudio descriptivo sobre la implicación de las familias en los cuidados de los ancianos institucionalizados

Abstract: El objetivo principal de este trabajo es conocer la implicación en los cuidados de las familias en la Residencia de Ancianos San Juan de Dios de Sevilla. Estudio piloto de corte cuantitativo, descriptivo y con carácter observacional. Tras un proceso de muestreo no probabilístico a conveniencia se ha conformado una muestra de 20 familiares de ancianos residentes, de los cuales 5 son hombres y 15 son mujeres. El instrumento para la recogida de datos es el cuestionario “Escala de sobrecarga del cuidador-Zarit”, y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
1
2
0
1
Order By: Relevance
“…With regard to the current conditions, both countries showed a larger number of interviewees visiting the older adult on a weekly basis, although this group is smaller in the Colombian sample, which may be due to the fact that a high proportion of Colombians live far from the residential facility, which is similar to the information reported by Pérez et al. (2015) .…”
Section: Discussionsupporting
confidence: 65%
“…With regard to the current conditions, both countries showed a larger number of interviewees visiting the older adult on a weekly basis, although this group is smaller in the Colombian sample, which may be due to the fact that a high proportion of Colombians live far from the residential facility, which is similar to the information reported by Pérez et al. (2015) .…”
Section: Discussionsupporting
confidence: 65%
“…Parece que los cuidadores siguen dando apoyo, atención y cuidados a su familiar tras la institucionalización 12 . Pérez et al 33 encontraron que el apoyo familiar de los mayores no cesa con la institucionalización. La implicación de los familiares en las residencias posee un fin colaborativo y de beneficio tanto para el propio residente, como para el cuidador familiar y los trabajadores del centro 15 .…”
Section: Discussionunclassified
“…We did not find research carried out in the Ibero-American environment that provided information on the type of kinship of family members visiting seniors admitted to nursing homes in terms of frequency because, as previously stated, research has been limited and qualitative research is most common. However, in Spain, Llamazares [ 48 ] found that only 2% of the family members were spouses; other authors have confirmed that along with siblings and other relatives, spouses constituted less than 10% of the sample [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation with standardized tools of the adaptation of the family member is practically absent in the literature. Only two studies have been found: one by Rosén et al [ 22 ] who evaluated quality of life using the World Health Organization’s quality-of-life self-assessment instrument (WHOQOL) in a sample of 254 family members in Sweden, and another work by Pérz-Dorado et al [ 23 ], who applied the “Zarit-caregiver burden scale” to a sample of 20 elderly relatives from a nursing home in Seville. However, quality of life is a broader concept than the adaptation of the family members, although they are interrelated and in the Spanish study with Zarit they found that, according to family members, there was no burden since the care for the elderly was in the hands of the nursing home staff; hence this questionnaire is of little use.…”
Section: Introductionmentioning
confidence: 99%